2013
DOI: 10.1177/0091829612475167
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and Intimacy between Sister Communities in El Salvador and the United States

Abstract: In this article I consider the desires of participants in a particular sister-community relationship. I suggest that experiences of Illinois parishioners who have been visiting, and assisting, rural Salvadorans over the past 20 years may help us to understand both the possibilities and the limits of such encounters. I probe the limits by examining an incident that took place in July 2010. In thinking through my discomfort with a request for money, in the context of a larger history of global relationships and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…As would be expected, some other research studies reveal areas of ambiguity and potential conflict that must be overcome in partnerships that connect individuals across socioeconomic lines (Bahamonde, 2007; Farrell, 2013; Moodie, 2013). Karla Knoll (2010: 93) rightly points out that STM “expresses in a graphic way the asymmetry in access to power and resources between most Christians in North America and our sisters and brothers in many other places.” Such differences and inequality naturally create distance.…”
Section: Impact On Partner Relationshipsmentioning
confidence: 64%
See 1 more Smart Citation
“…As would be expected, some other research studies reveal areas of ambiguity and potential conflict that must be overcome in partnerships that connect individuals across socioeconomic lines (Bahamonde, 2007; Farrell, 2013; Moodie, 2013). Karla Knoll (2010: 93) rightly points out that STM “expresses in a graphic way the asymmetry in access to power and resources between most Christians in North America and our sisters and brothers in many other places.” Such differences and inequality naturally create distance.…”
Section: Impact On Partner Relationshipsmentioning
confidence: 64%
“…And it is such patterns of mobility and global connectedness that characterize 21st-century mission.” Few studies on STM, however, assess the impact on the participants who go and the individuals who host them in terms of the partnerships they develop. Several studies have focused on the possibility of linking social capital (Bahamonde, 2007; Priest, 2008; Offutt, 2011; Priest, 2007; Wuthnow, 2009) while others have explored the socioeconomic dynamics prevalent in partnerships between sister churches that engage in STM (Bakker, 2014; Brown, 2008; Farrell, 2013; Hefferan, 2007; Moodie, 2013; Reeves, 2007). As would be expected, the majority of research studies exploring the impact of STM within a partnership model generally show a widespread positive effect on both participants and hosts.…”
Section: Impact On Partner Relationshipsmentioning
confidence: 99%
“…The responses to the open-ended invitation to name the goals, values, and/or principles indicated that personal friendships and spiritual fruits were just as important to the respondents as works of mercy. Clearly, as Ellen Moodie wrote (2013: 158–62), people engage in these partnerships because they yearn for personal connection with those of their partnering parish (and Moodie specifically notes the “otherness” as part of that attraction).…”
Section: Discussionmentioning
confidence: 99%
“…Some Catholic parish partnerships have done this to some extent, but many partnerships do not challenge subtle stereotypes, particularly around race and class. Without formation that includes confronting stereotypes and false assumptions, true relationships with partners will be illusory, as suggested by Moodie (2013: 160). Indeed, it may exacerbate those very stereotypes and assumptions.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation